2005
DOI: 10.1007/s00234-005-1383-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced FLAIR in the early diagnosis of infectious meningitis

Abstract: We investigated the accuracy of MRI in the early diagnosis of infectious meningitis with emphasis on the value of gadolinium-enhanced fluid-attenuated inversion recovery (FLAIR) sequence. Twenty-seven patients with clinical suspicion of infectious meningitis were included. MRI was performed within 3 h of clinical evaluation. For all patients, T1-weighted spin-echo, dual-echo T2-weighted fast-spin-echo and FLAIR sequences were performed, followed by gadolinium-enhanced T1-weighted spin-echo and FLAIR sequences.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 20 publications
4
69
1
2
Order By: Relevance
“…One advantage of ceFLAIR compared to ceT1W images in extra‐axial lesions is better differentiation of enhancing meninges from cortical veins because slow‐flowing blood is usually not hyperintense on ceFLAIR 9, 10, 13, 15, 16, 26. This could be an argument for a supplemental ceFLAIR sequence, but recent studies have shown that a ceT1W sequence with fat suppression is superior to ceFLAIR for meningeal lesions because it combines the advantages of suppression of the fat signal with shortening of T1 relaxation time 23, 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One advantage of ceFLAIR compared to ceT1W images in extra‐axial lesions is better differentiation of enhancing meninges from cortical veins because slow‐flowing blood is usually not hyperintense on ceFLAIR 9, 10, 13, 15, 16, 26. This could be an argument for a supplemental ceFLAIR sequence, but recent studies have shown that a ceT1W sequence with fat suppression is superior to ceFLAIR for meningeal lesions because it combines the advantages of suppression of the fat signal with shortening of T1 relaxation time 23, 27.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the T2 relaxation time of the lesion itself also influences signal intensity in ceFLAIR, lesion visibility might be reduced in some cases 8. As a result, the diagnostic value of ceFLAIR to detect brain disease in human medicine is controversial 9, 10, 11, 12, 13, 14, 15, 16, 17. In veterinary medicine, ceFLAIR is superior to precontrast FLAIR sequences (nFLAIR) and contrast‐enhanced T1‐weighted (ceT1W) sequences for the detection of brain lesions 5.…”
mentioning
confidence: 99%
“…Although postcontrast 2D T2-FLAIR imaging was reportedly useful for assessing anomalies in the leptomeningeal space, [1][2][3][4] concerns regarding its utility have been raised. 10,11 CSF pulsation artifacts on 2D T2-FLAIR images may render the detection of lesions in the CSF spaces difficult.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Three-dimensional T2-FLAIR sequences with a nonselective inversion pulse can be acquired in a clinically acceptable scan time by using the variable flip-angle technique in a 3D turbo spin-echo sequence. [5][6][7][8] As 3D T2-FLAIR imaging yields 3D volume data with isotropic information, thinner section images can be acquired in any plane; this minimizes the partial volume effect between small lesions and surrounding tissue.…”
mentioning
confidence: 99%
“…Sekarang ini, MRI kepala sekuens T2 fluid attenuated inversion recovery dengan pemberian kontras gadolinium-DTPA (selanjutnya disebut T2-FLAIR post contrast) banyak diteliti oleh para ahli untuk mendeteksi keberadaan penyangatan meningeal pada meningitis TB. 14,15 Pada penelitian yang telah dilakukan oleh Splendiani dkk.…”
Section: -13unclassified